Radiological correlation with functional outcome in displaced proximal humerus fractures treated with locking plates: a prospective study of 35 cases - Mahajan, Neetin Pralhad; Palange, Nikhil Dilip; Pawar, Eknath D.; Jivrajbhai Mangukiya, Hitesh; Ramteke, Ujwal Suryabhan; Ravesh, Vedashish; Jadhav, Umesh; G. S., Prasannakumar (International Journal of Research in Orthopaedics, 2018)
Background: The objective of this prospective study is to investigate the relationship between the functional outcome and the radiographic results of two-, three- and four part proximal humeral fractures treated with open reduction and fixation with PHILOS locking plate. Methods: 35 patients (30 males and 5 females) with displaced proximal humerus fracture were treated with PHILOS plating and studied prospectively. According to Neer’s classification there were 16 two part fracture (45%), 15 three part fracture (42%) and 4 four part fracture (13%). The healing of fracture, head shaft angle (HSA) and complications were evaluated radiologically with plain radiographs whereas the functional outcome was assessed by the Shoulder Pain and Disability Index (SPADI) at 6 weeks, 3 months, 6 months and 1 year after surgery. Results: In our study, patients treated with locking plates had mean forward flexion of 123°, abduction of 124°, mean external rotation of 30° and internal rotation 53° at 1 year follow-up. Maximum improvement in range of movement occurred between interval of 12 weeks to 24 weeks due to complete fracture union occurred approximately up to 12 weeks. The mean SPADI score at end of 1 year were 10.22, 10.38 and 10.20 for two, three and four part fractures respectively. Average postoperative and follow-up HSA’s were 134.1±4.4 and 132.5±1.2 degrees, respectively. Varus progression was more prominent in patients with postoperative HSA <130 (p<0.001). Complications included impingement in 1 case, joint penetration by screw in 1 case, failure of fixation in 1 case and infection in 1 case. Conclusions: Fixed angle locked plate is an extremely useful implant for reconstruction and salvage of proximal humeral fractures. Precise surgical technique, stable fracture fixation and restoration of anatomical reduction are absolutely necessary for improved outcome.